A genome-wide association study identifies susceptibility loci for nonsyndromic sagittal craniosynostosis near BMP2 and within BBS9 - Justice, C; Yagnik, G; Kim, Y; Peter, I; Jabs, E; Erazo, M; Ye, X; Ainehsazan, E; Shi, L; Cunningham, M; Kimonis, V; Roscioli, T; et al. (2012)
Sagittal craniosynostosis is the most common form of craniosynostosis, affecting approximately one in 5,000 newborns. We conducted, to our knowledge, the first genome-wide association study for nonsyndromic sagittal craniosynostosis (sNSC) using 130 non-Hispanic case-parent trios of European ancestry (NHW). We found robust associations in a 120-kb region downstream of BMP2 flanked by rs1884302 (P = 1.13 × 10-14, odds ratio (OR) = 4.58) and rs6140226 (P = 3.40 × 10-11, OR = 0.24) and within a 167-kb region of BBS9 between rs10262453 (P = 1.61 × 10-10, OR = 0.19) and rs17724206 (P = 1.50 × 10-8, OR = 0.22). We replicated the associations to both loci (rs1884302, P = 4.39 × 10-31 and rs10262453, P = 3.50 × 10-14) in an independent NHW population of 172 unrelated probands with sNSC and 548 controls. Both BMP2 and BBS9 are genes with roles in skeletal development that warrant functional studies to further understand the etiology of sNSC. © 2012 Nature America, Inc. All rights reserved.